Different paths to the same place: late modern narrative identities in a South African Business School - Prangley, Anthony Ross (My University, 2021)
Late modernity and globalisation have re-oriented group dynamics and situated the self in new relational settings. With these changes, identity-oriented political movements and more personal identity processes have become the focus of much theorising. A key strand of this theorising has focused on the role of narrative in organising personal identity. This study applied key strands of this narrative theorising to interpret the intergenerational life-stories of a group of 55adult learners returning to formal studies in a South African Executive Master of Business Administration programme. Under late modernity, navigating the life-course has been theorised as increasingly complex. The study context can be seen as a holding environment for the reflexive identity work associated with the risks and opportunities of contemporary adult life. These stories highlighted the salience of religion, family loyalty, educational aspirations, gender dynamics and boundary negotiation. By taking a narrative approach, I defined the intergenerational upward and downward paths, interesting script elements, and agency and structure dynamics. A set of six archetypal storylines were identified. In order to connect the study to a broader context, the findings were made more nuanced by an analysis of five recently published autobiographical books from publicly engaged South Africans of the same age. This study makes three important theoretical contributions. Firstly, it contributes to the scholarship of self and society under late modern conditions, by bringing a transitioning society and African perspective to these debates. In the study context, I demonstrate a number of coherent themes and show that modern themes act as a centripetal force against late modern fragmentation. I show the expansive and challenging demands of cross-boundary encounters. I argue that shifting stories that ‘have us’ to stories ‘we have’ can potentially enable collective autonomy. Secondly, the study shows the value of the narrative approach in this context. I propose two new codes to account for the local realities: Family-based agency and God and faith. Without this vocabulary, existing frameworks were found to be inadequate. Shifts in place and space acted as chapters in the stories present. More research is needed in the African context on‘ far ancestral’ and ‘royalty-linked’ script elements. Business schools are one of the fastest growing and most influential locations for late modern adult learning. Yet, business school scholarship has yet to substantively consider self and identity processes associated with narrative identities–especially in their social context. The third contribution of this study is to show how narrative identity can matter for business school teaching and learning – especially in leadership and career development
A thesis submitted in fulfilment of the requirements of the degree of Doctor of Philosophy (PhD) in the Department of Sociology, Faculty of Humanities, University of the Witwatersrand, 2021